Phenology, vegetative growth, and yield performance of fig in Southeastern Brazil - Ferraz, Rafael Augusto; Leonel, Sarita [UNESP]; Azevedo Souza, Jackson Mirellys [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Modesto, Joyce Helena [UNESP]; Arruda, Lucas Lencioni [UNESP] (Empresa Brasil Pesq Agropec, 2020)
The objective of this work was to evaluate the phenological patterns, vegetative growth, and yield characteristics of fig (Ficus carica) varieties in Southeastern Brazil. The 'Roxo de Valinhos', White Genova, PI-189, and Troyano varieties were distributed in a randomized complete block design and evaluated in the field. The following characteristics were assessed: number of days between pruning and the beginning of sprouting; leaf chlorophyll content; number of shoots on each branch; length, diameter, and number of internodes on each branch; number of leaves per plant; leaf area; number of fruit per plant; mass, length, and diameter of fruit; production and yield; and duration (days) of each phenological stage, such as thermal requirement models. 'Roxo de Valinhos' and White Genova sprouted the fastest and showed the largest number of shoots. Troyano obtained the greatest branch length and diameter, as well as the greatest number of fruit per plant, which had the shortest diameter and length and the lowest mass of fruit. Furthermore, Troyano showed the latest harvest, besides the thermal requirement of 4,577.31 degree-days. 'Roxo de Valinhos' and White Genova produced fruit with the greatest average mass and diameter and the longest length. Troyano shows better vegetative growth and produces more fruit per plant than 'Roxo de Valinhos', but both genotypes show similar yields.
Keywords: Ficus carica; degree-days; leaf area; production; pruning